DIAGNOSIS OF THIRD MOLAR EXTRACTION - Kozima, Rafael Kenzo; de Brito, Isabele Natali Araujo (Seven Editora, 2026)
Third molar (3M) extraction is one of the most frequently performed procedures in oral and maxillofacial surgery. The decision to intervene is based on an accurate diagnosis that assesses associated pathologies, such as pericoronitis and caries in the adjacent second molar, in addition to classifying surgical complexity. This study is a narrative literature review that sought to synthesize and examine current scientific evidence regarding the diagnosis of third molar extraction. Data collection was performed in the PubMed database using the descriptors "Third Molar Extraction" AND "Diagnosis". The results highlight imaging diagnosis as a central pillar. Cone Beam Computed Tomography (CBCT) is the gold standard for cases of radiographic overlap, allowing the evaluation of the relationship with important structures, such as the inferior alveolar nerve, and predicting surgical difficulty through classifications such as Pell & Gregory and Winter. The association of impaction patterns and secondary pathologies, such as pericoronitis and distal caries in the second molar, is a determining factor for the indication of surgery. The diagnosis must be individualized, considering the anatomical complexity and systemic profile of the patient, weighing the use of systemic antibiotic prophylaxis, whose routine application in healthy patients is debated in light of the risk of bacterial resistance.